Optimizing Fundraising: Philanthropy Education as an Innovative Approach to Increase LAZ and BAZNAS Contributions - Zulaekah; Nina Mariani Noor (Arbain Publishing, 2025)
Optimizing fundraising is a critical challenge for Islamic philanthropic institutions like LAZ (Lembaga Amil Zakat) and BAZNAS (Badan Amil Zakat Nasional) in Indonesia. Despite their significant potential, these organizations often face barriers in maximizing their fundraising efforts due to limited public awareness and understanding of their mission. This study aims to explore the role of philanthropy education as an innovative approach to increase the contributions to LAZ and BAZNAS. Using a qualitative research approach and literature study method, this paper examines existing literature on philanthropy education, its impact on donor behavior, and strategies for effectively integrating it into Islamic fundraising models. The findings indicate that philanthropy education can significantly enhance donor awareness, foster a culture of giving, and strengthen the financial sustainability of LAZ and BAZNAS. Educating the public about the social and spiritual benefits of zakat, infaq, and sadaqah can transform potential donors into active contributors. Additionally, integrating philanthropy education into community outreach, school curricula, and digital platforms can broaden the donor base and encourage long-term commitment to charitable giving. This study concludes that philanthropy education is a promising strategy for optimizing fundraising, requiring coordinated efforts from Islamic institutions, government agencies, and educational organizations. Further research is recommended to assess the practical impact of these educational approaches in different community settings and to develop tailored strategies that address the unique challenges faced by LAZ and BAZNAS in the digital era.